Natural antimicrobials for beet leaves preservation: in vitro and in vivo determination of effectiveness - Fernandez, María Verónica (2018)
Nisin (Ni), natamycin (Na), green tea extract (GTE) and their combinations were evaluated for controlling beet leaves’ native microbiota as well as Listeria innocua and Escherichia coli external contaminations. Antimicrobial effectiveness was evaluated through in vitro and in vivo studies. In the in vitro studies, GTE treatment (0.85%) completely eliminated growth of native microbiota, reduced L. innocua from values of 8.5–3.5 log from 24 h onwards and reduced E. coli below detection limit (DL) after 72 h. Ni (500 IU/mL) was the most effective against L. innocua (7 log CFU/mL reduction) and its combination with GTE presented significant interactions for mesophilic aerobic bacteria (MAB) and L. innocua control. Na (200 ppm) alone or in combination with GTE did not show antimicrobial activity against microorganisms under study. Additionally in vivo evaluation showed that 2.5–5% GTE concentrations are needed to achieve significant inhibitory effects on MAB, L. innocua and E. coli. Furthermore, the best results for MAB and L. innocua control were obtained with the GTE5 + Ni treatment. This study revealed that GTE, either alone or combined with nisin, is a highly promising option with potential for reducing or preventing the growth of pathogenic and spoilage microorganisms present in leafy vegetables, specifically in beet leaves.